Congenital cytomegalovirus infections and glycoprotein B genotypes in live-born infants: a prevalence study in Turkey. Issue 7 (July 2015) - Sahiner, Fatih; Cekmez, Ferhat; Cetinkaya, Merih; Kaya, Guven; Kalayci, Tugce; Gunes, Omer; Sener, Kenan; Yapar, Mehmet; Tunc, Turan; Ecemis, Tolga; Cekmez, Yasemin; Kubar, Ayhan
Abstract: Background: Cytomegalovirus (CMV) infections are the leading cause of infectious hearing loss and central nervous system disease among children worldwide. In this study, we aimed to determine the birth prevalence of congenital CMV infection in live-born infants in Turkey. Methods : In total, 944 consecutive live-born infants born from 926 pregnant women were included in this study. CMV-DNA was investigated in saliva samples of all newborns within the first 3 days after birth using TaqMan-based real-time PCR. Results: The birth prevalence of congenital CMV infection in live-born infants was 1.91% (18/944), and all congenitally infected infants were asymptomatic at birth. The prevalence of congenital CMV infection was 16.7% (3/18) in twin pregnancies and 1.32% (12/908) in single pregnancies ( p = 0.002). Genotyping analysis showed glycoprotein B-1 (gB1) to be the most frequently detected genotype at 83.3%. Conclusion: The study results suggest that the majority of congenital CMV infection in Turkey occurs following nonprimary maternal infection. We believe that congenital CMV infection and its long-term effects have been underestimated in our country, as infected infants are usually asymptomatic at birth.